2003
DOI: 10.1093/cercor/13.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Fast-spike Interneurons and Feedforward Inhibition in Awake Sensory Neocortex

Abstract: 'Fast-spike' interneurons of layer 4 mediate thalamocortical feedforward inhibition and can, with some confidence, be identified using extracellular methods. In somatosensory barrel cortex of awake rabbits, these 'suspected inhibitory interneurons' (SINs) have distinct receptive field properties: they respond to vibrissa displacement with very high sensitivity and temporal fidelity. However, they lack the directional specificity that is clearly seen in most of their ventrobasal thalamocortical afferents. Sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
252
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(284 citation statements)
references
References 60 publications
31
252
0
1
Order By: Relevance
“…This does not imply that all such neurons must be nonselective (see refs. [40][41][42][43][44][45]. For instance, the results of ref.…”
Section: Discussionmentioning
confidence: 99%
“…This does not imply that all such neurons must be nonselective (see refs. [40][41][42][43][44][45]. For instance, the results of ref.…”
Section: Discussionmentioning
confidence: 99%
“…Neurons in the present study were classified as RS, FS, or "unspecified" based on analysis of their extracellular spiking features, but only RS and FS neurons were included in this analysis. Combined morphological and physiological studies have revealed that in most instances RS and FS neurons may be reliably identified as pyramidal neurons and inhibitory interneurons, respectively (McCormick et al, 1985;Rao et al, 1999;Tanaka, 1999;Compte et al, 2000;Constantinidis and Goldman-Rakic, 2002;Swadlow, 2003;Isomura et al, 2009). "Baseline firing rate" was defined as the average firing rate recorded from a neuron when the animal was sitting quietly.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have distinguished spiny (excitatory) and nonspiny (inhibitory) neurons based on characteristics of extracellular spikes (McCormick et al, 1985;Kawaguchi, 1995;Cauli et al, 1997;Rao et al, 1999;Compte et al, 2000;Constantinidis and Goldman-Rakic, 2002;Swadlow, 2003;Isomura et al, 2009). Studies investigating functional interactions between fast-spiking (FS, interneuron) and regular-spiking (RS, pyramidal) neurons in motor and nonmotor areas of cerebral cortex have shown that the incidence of these interactions can vary between different neuronal subtypes (Rao et al, 1999;Tanaka, 1999;Compte et al, 2000;Constantinidis and Goldman-Rakic, 2002;Swadlow, 2003;Merchant et al, 2008;Isomura et al, 2009). Again, similar studies are yet to be performed during different behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…First, FS cells are fast-spiking, which, we speculate might mean that they contribute more to the ambient concentration of GABA than LTS cells. Second, FS cells receive direct thalamocortical input (Gibson et al, 1999;Beierlein et al, 2000;Porter et al, 2001;Swadlow, 2003), which puts them in a more direct position to be regulated by thalamocortical bursting than LTS cells. Finally, FS cells are inhibited, whereas LTS cells are excited, by acetylcholine (Xiang et al, 1998).…”
Section: From Steriade To the Futurementioning
confidence: 99%
“…Large bundles of fibers from the bar-reloids in the ventral posterior medial nucleus of the thalamus project to individual barrels in layer 4 (Woolsey and Van der Loos, 1970). These thalamocortical fibers synapse onto excitatory neurons and onto a type of inhibitory interneuron neuron (White and Keller, 1987) called fast-spiking (FS) cells that mediate feed-forward inhibition (Porter et al, 2001;Swadlow, 2003). Thus, inhibition is recruited at a very early stage in sensory processing.…”
Section: Introductionmentioning
confidence: 99%